USING CONSUMER-GRADE DSLR CAMERA AND SMALL TELESCOPE TO FIND NEW VARIABLE STARS - Pyatnytskyy, M. Yu. (Одеські астрономічні публікації, 2019)
Twenty-seven new variable stars were found in DSLR images captured from October 2017 to June 2019. All images were taken using unmod- i?ed Canon EOS 600D DSLR attached to a Sky- watcher 150/750 Newtonian on a motorized equato- rial mount. The variables were registered in The In- ternational Variable Star Index (VSX, AAVSO) as PMAKV1..PMAKV27 respectively. Most of them (twelve) were classi?ed as semiregular variables of dif- ferent subtypes, nine as eclipsing binaries (EA, EW, and EB), three rotating RS Canum Venaticorum-type stars, one rotating ellipsoidal variable (ELL), one Delta Scuti-type pulsating variable, and one as a possible nova-like (NL) star. The setup and methodology used by the author al- lowed discovering of variables having a wide range of maximum brightness (from 8: m 9 to 14: m 4 in V band for stars described in the current work), variability range up to ?0: m 1 and less, and quite di?erent periods of vari- ability, from hours to hundreds of days. Although all those variables were detected using images taken by the author, detailed analysis and classi?cation of stars re- quired the involvement of additional data sources (au- tomated sky surveys